Diversity and phylogeny of the brown alga Lobophora (Dictyotales, Phaeophyceae) in Singapore - Kwan, Valerie; Yip, Zhi Ting; Fong, Jenny; Huang, Danwei (Phytotaxa, 2021)
The brown macroalgal genus Lobophora (Phaeophyceae: Dictyotaceae) plays an ecologically significant role in many marine ecosystems, but their diversity and taxonomy remain poorly studied. Until 2012, six Lobophora species had been recognised globally based on morphological features. Yet, with more than 100 evolutionary taxonomic units characterised to date, it is now acknowledged that Lobophora comprises many cryptic species and its diversity was vastly underestimated. In light of a growing body of research integrating molecular and morphological data to delimit cryptic species, this study assessed the diversity and phylogeny of Lobophora in Singapore. A combination of molecular data and morphological observations were used to delimit and identify species from 33 specimens collected at eight sites in the southern islands of Singapore. The mitochondrial cox3 and chloroplast psbA genes were amplified and sequenced for phylogenetic analysis. Three formally described species, L. challengeriae, L. lamourouxii, L. pachyventera (comprising two morphotypes), as well as one undescribed putative species, Lobophora sp61, were recovered. These findings replace the record of the Atlantic species L. variegata in Singapore and suggest that there are more species to be discovered in the biodiverse region of Southeast Asia. Precise understanding of Lobophora diversity is critical for ongoing and future work on coral–macroalgal ecological relationships.